Are More College Graduates Necessary? (International Journal of Innovative Research in Engineering & Management, 2021)
President Barack Obama has launched a  new initiative to boost the proportion of young people with  a college degrees. More degrees would be advantageous if  more low-income students obtained them, according to the  report, since social mobility may be difficult without one.  When substantial external factors such as high school  quality, family income and wealth, and parent educational  background are included, the work becomes more  challenging (s). According to the research, early  intervention measures have the best likelihood of boosting  the number of degree holders from low-income families.  Since then, the White House has taken a number of steps  to help in the completion of the work. The president  donated the bulk of his $1.4 million Nobel Peace Prize to  six groups that support underprivileged students' access to  higher education, indicating his commitment to increasing  the number of graduates.
Keywords: Competition Rates; College Graduate; Degrees; Early Intervention; Employment